The plant volatile attractant (E,Z) - 2,4-ethyl-decadienoate (DA2313) for Codling Moth monitoring (Bollettino di zoologia agraria e bachicoltura, 2024)
Trials have been carried out to assess the potential of (E,Z)-2,4-ethyldecadienoate (DA2313) for monitoring Cydia pomonella (CM). DA2313 baitedtraps were attractive for males and females even though the total number of catchesis lower compared to the synthetic pheromone (E,E)-8, 10-dodecadienol.DA2313 baited traps catch a significantly higher number of insects when placedat the top of the trees (3.5-4.0 m) rather than at the height of 2 m, the oppositeof what can be observed for pheromone traps. Traps with a wider sticky basecatch much more females than standard size traps.
Keywords: Cydia pomonella; plant volatiles; DA2313, (E,Z)-2,4-ethyl decadienoate; pheromone; monitoring; pome fruits